THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHER IN DEVELOPING STUDENTS' RELIGIOUS ATTITUDE AT SMK PAB 1 HELVETIA - Parida Hanum Munthe; Rahmat Hidayat; Muhammad Aqsho (Universitas Dharmawangsa, 2023)
Teachers have part of the responsibility of parents to provide education, when children are delegated to teachers at school. Teachers are parents of students at school. As parents in schools, teachers should be responsible for the development of students, both cognitive, affective and psychomotor. Especially for Islamic Religious Education Teachers (PAI) who have a duty not only to transfer knowledge but also play a role in providing teaching and guidance related to students' religious attitudes. This study uses a qualitative approach, so that the main instrument in this study is the researcher. Data collection by observation and interviews. The results showed that the teacher has a role as corrector, inspiratory, informatory, organizer, motivator, initiator, facilitator, supervisor, class manager, and mediator. These many roles can make students have role models and can internalize religious values in them.